BILINGUAL TRAINING AS A CONDITION FOR INTEGRATING INTO GLOBAL EDUCATION - T. Danilova (Вестник Северо-Кавказского федерального университета)
The relevance of this article is determined by the need to identify the role of bilingual training in the context of the globalization of education. The article is aimed at the analysis of global education in its development dynamics and identifying the opportunities of bilingual training in the process of forming the competitiveness of future graduates of a higher educational institution. The purpose of the article is to reveal the essential characteristics of bilingual training as a form of reflection of integration processes in the world culture and education as well as to update the didactic and methodological foundations of the creation of bilingual programs (curriculums) as a means offorming communicative competence and the competitiveness of a professional in the educational paradigm of a modern university.